Efektivitas Manajemen Pembelajaran Berbasis Teknologi Informasi dan Komunikasi di SMP Negeri Kota Pematang Siantar - Fitri Ratnasari; Sri Nurabdiah Pratiwi; Faisal R Dongoran (UMSU, 2023)
This study aims to, (1) To know the Information and Communication Technology-Based Learning Planning Process at Pematang Siantar City State Junior High School. (2) To know the Process of Implementing Information and Communication Technology-Based Learning at Pematang Siantar City State Junior High School. (3) To determine the evaluation of Information and Communication Technology-Based Learning at Pematang Siantar City State Junior High School. (4) To find out whether there is an improvement in student learning outcomes after teachers apply Information and Communication Technology-Based learning management at Pematang Siantar City State Junior High School. The approach is used mixed method. The design used in this study is The exploratory sequential design. The design of the sequential exploratory is in the first stage the researcher collects and analyzes data in the form of qualitative, then in the second stage collects quantitative data based on the results of the first stage. Some of the subjects that were studied. Some of the subjects used as data sources in this study are: principals, teachers, and students in four (SMP Negeri 1 Pematang Siantar, SMP Negeri 2 Pematang Siantar, SMP Negeri 4 Pematang Siantar, and SMP Negeri 8 Pematang Siantar) Pematang Siantar, North Sumatea Province. The results showed that there was an Activity of Information and Communication Technology-Based Learning Management in the planning process, implementation process, learning evaluation and there was an increase in student learning outcomes after teachers implemented Information and Communication Technology-Based Learning Management at SMP Negeri Kota Pematang Siantar. From data analysis, it is known that the effectiveness of information and communication technology-based learning management at Pematang Siantar City State Junior High School has been effective.